Evolving Frameworks in Digital Payment Security: Technological Innovations, Economic Impact, and Consumer Trust Dynamics - Utham Kumar Anugula Sethupathy (International Journal of Computational and Experimental Science and Engineering, 2025)
Digital payment ecosystems have transformed financial transactions worldwide. These systems evolved from early credit card technologies to today’s sophisticated mobile and contactless platforms. This article examines the fundamental security technologies underpinning modern digital payments. Key mechanisms include tokenization, encryption, biometric authentication, and artificial intelligence-driven fraud detection. These complementary security frameworks create multiple defensive layers protecting financial information throughout transaction lifecycles. Implementations across various contexts demonstrate their practical impact on both security posture and user experience. Beyond fraud prevention, secure digital payments have generated substantial economic benefits. They reduce transaction friction, enable financial inclusion, and create new commercial opportunities, particularly in emerging markets. Regulatory frameworks continue to evolve alongside these technological advancements. They balance security mandates with innovation incentives while addressing cross-jurisdictional challenges. Consumer trust remains critical to adoption, with perceived security significantly influencing payment method selection. The article highlights how security technologies protect financial data while fostering trust necessary for continued digital payment adoption in an increasingly connected global economy.